Business valuation: The case of a hotel in Costa Rica - Paniagua Molina, Javier (2018)
The objective of the study was to determine the value of a hotel with a long history in Costa Rica, considering the value of physical assets such as land, buildings, furniture and equipment, as well as the value of the hotel business.  The results showed how the hotel business represents about 15% of the value of the land, which indicates that it may be necessary to rethink the competitive strategy to create greater value for the company, or the land must be used for other alternative commercial uses.  It is expected that the methodology presented here could serve as a guide for the valuation of hotel businesses in rural areas.